Mini Review: Controlling of Blood Glucose Levels Utilizing Lactic Acid Bacteria - Fatmawati Nur; Hafsan; Faten Khudair (Jurusan Biologi Universitas Negeri Makassar, 2023)
Lactic acid bacteria (LAB) interest promises a prospective dietary approach for enhancing the management of blood sugar levels in individuals diagnosed with diabetic and those presenting with pre-diabetic conditions. This review article summarizes the available evidence on the role of LAB in blood sugar regulation, focusing on the mechanisms underlying its effects and relevant research results. LAB supplementation has been shown to improve glucose tolerance and insulin sensitivity in animal and human studies, as well as to reduce fasting blood glucose levels in individuals with type 2 diabetes. Potential mechanisms underlying the effects of LAB on blood glucose control include improving insulin sensitivity, reducing inflammation, and improving intestinal barrier function. However, further supporting studies are needed to fully understand the optimal strain and dose of LAB for blood glucose control and to elucidate the mechanisms by which they exert their effects. Despite promising results, the safety and potential side effects of LAB supplements should also be carefully considered. Overall, this review highlights the potential of LAB as a dietary strategy for blood sugar regulation in individuals with diabetic and pre-diabetic.